Bias in binge eating disorder: how representative are recruited clinic samples? - Wilfley, D; Pike, K; Dohm, F; Striegel-Moore, R; Fairburn, C (2001)
The aim of this study was to investigate sampling bias as it affects recruited clinic samples of binge eating disorder (BED). Demographic and clinical characteristics of a recruited clinic sample were compared with a community sample. The 2 groups met the same operational definition of BED and were assessed using the same primarily interview-based methods. Ethnicity, severity of binge eating, and social maladjustment were found to increase treatment seeking among participants with BED rather than levels of psychiatric distress or comorbidity. These findings suggest that previous studies using recruited clinic samples have not biased estimates of psychiatric comorbidity in BED.